Indifference or hypersensitivity? Solving the riddle of the pain profile in individuals with autism. Issue 4 (26th April 2023) - Hoffman, Tseela; Bar-Shalita, Tami; Granovsky, Yelena; Gal, Eynat; Kalingel-Levi, Merry; Dori, Yael; Buxbaum, Chen; Yarovinsky, Natalya; Weissman-Fogel, Irit
Abstract : Supplemental Digital Content is Available in the Text. Individuals with autism show that a pronociceptive profile comprises facilitative state and less efficient inhibition of tonic pain attributed to disease severity and sensory modulating disturbances. Abstract: Excitatory–inhibitory (E/I) imbalance is a mechanism that underlies autism spectrum disorder, but it is not systematically tested for pain processing. We hypothesized that the pain modulation profile (PMP) in autistic individuals is characterized by less efficient inhibitory processes together with a facilitative state, indicative of a pronociceptive PMP. Fifty-two adults diagnosed with autism and 52 healthy subjects, age matched and sex matched, underwent quantitative sensory testing to assess the function of the (1) pain facilitatory responses to phasic, repetitive, and tonic heat pain stimuli and (2) pain inhibitory processes of habituation and conditioned pain modulation. Anxiety, pain catastrophizing, sensory, and pain sensitivity were self-reported. The autistic group reported significantly higher pain ratings of suprathreshold single ( P = 0.001), repetitive (46°C- P = 0.018; 49°C- P = 0.003; 52°C- P < 0.001), and tonic ( P = 0.013) heat stimuli that were cross correlated ( r = 0.48-0.83; P < 0.001) and associated with sensitivity to daily life pain situations ( r = 0.39-0.45; P < 0.005) but not with psychological distress levels. Hypersensitivity to experimental pain was attributed to greater autism severity and sensory hypersensitivity to daily stimuli. Subjects with autism efficiently inhibited phasic but not tonic heat stimuli during conditioned pain modulation. In conclusion, in line with the E/I imbalance mechanism, autism is associated with a pronociceptive PMP expressed by hypersensitivity to daily stimuli and experimental pain and less-efficient inhibition of tonic pain. The latter is an experimental pain model resembling clinical pain. These results challenge the widely held belief that individuals with autism are indifferent to pain and should raise caregivers' awareness of pain sensitivity in autism.